Documenta : Idee und Institution : Tendenzen - Konzepte - Materialien - Schneckenburger, Manfred (München : Verlag F. Bruckmann KG, 1983)
Kirchner, Ernst Ludwig ; Blumenthal, Hermann ; Vostell, Wolf ; Thek, Paul ; Paik, Nam June ; Penck, A.R. ; Borofsky, Jonathan ; etc.
boek